(untitled) (Research, Society and Development, 2021)
Introduction: With the creation of the Sistema Único de Saúde (Unified Health System) - SUS, through Primary Health Care (PHC), the population has access to a multidisciplinary health environment, capable of meeting the most varied demands, especially with regard to Diseases Non-Communicable Chronicles (DCNT). In this context, complications arising from the diabetic foot need special attention, as they still have a high incidence and its complications significantly affect the lives of patients. Objectives: To analyze the impact of actions taken to care for patients with diabetic foot by the PHC, emphasizing the importance of training health professionals. Methodology: This is an integrative review with a qualitative approach, using the databases BVS, SciELO and MEDLINE, using the descriptors “health professionals”; “health education”, “diabetic foot” and “primary care”. Among the inclusion criteria are scientific articles in Portuguese, English and Spanish published between the years 2010 to 2021, as an exclusion criterion we had duplicate articles that were unable to answer the problem and objectives of the theme. 58 articles were found, and in the end 8 articles were analyzed. Final Considerations: After carrying out this study, we concluded that the development of activities that encompass health education aimed at health professionals in PHC has positive impacts on the prevention and management of patients with diabetic foot. However, there are many barriers that hinder this process, requiring greater human, financial and technological investments in this area.